Cross cultural management challenges in the internationalisation activities of Medellin's SMES [Desafios de gestão intercultural nas actividades de internacionalização de micro-empresas de Medellín] [Retos de gestión intercultural en las actividades de internacionalización de microempresas de Medellín] (2013)
This document analyses cross-cultural management challenges in the internationalisation activities of small to medium enterprises in Medellin, Colombia. Electronic questionnaires were used to collect information from five micro-enterprises in the services industry. Their responses were subsequently studied using a partially ordered meta-matrix using an analytical-synthetic method. The work differs from others that focus on business skills for survival, because it emphasises in exploring advanced skills related to growth and profitability, that is, cross-cultural management in international management. Eleven challenges are listed to describe the capabilities that SME's in Medellin must build on to make its internationalisation activities more effective. © 2013 Universidad ICESI. Published by Elsevier España. All rights reserved.